Chin Reshaping in Profileplasty: Augmentative and Reductive Strategies - Eppley, Barry L. (Facial Plastic Surgery, 2019)
After studying this article, the reader should be able to understand how various implants, osteotomies, and reductive tissue techniques affect the aesthetic outcomes of chin reshaping surgery. The roles of standard versus custom chin implants, the operative steps and indications for a bony genioplasty and the techniques for chin reduction are described with emphasis on proper patient selection and avoiding their common complications.
Keywords: chin implant; sliding genioplasty; chin reduction; custom chin implant; chin ptosis correction